Andrei Tarkovsky's Solaris - Lem, Stanisław 1921-2006; Artemʹev, Ėduard Nikolaevič 1937-2022 (<<The>> Criterion Coll., 2011)
"Ground control has been receiving strange transmissions from the three remaining residents of the Solaris space station. When cosmonaut and psychologist Kris Kelvin is sent to investigate, he experiences the strange phenomena that afflict the Solaris crew, sending him on a voyage into the darkest recesses of his own consciousness. In Solaris, legendary Russian filmmaker Andrei Tarkovsky creates a brilliantly original science fiction epic that challenges our preconceived notions of love, truth, and humanity itself."--Publisher's Web site.
Bildformat 2.35:1. - High definition digital restauration
Orig.: Sowjetunion 1972
Enth. audio commentary by Andrei Tarkovsky scholars Vida Johnson and Graham Petrie ; nine deleted and alternate scenes ; video interviews with actress Natalya Bondarchuk, cinematographer Vadim Yusov, art director Mikhail Romadin and composer Eduard Artemyev ; excerpt from documentary about Stanislaw Lem, the author of the film's source novel